Social entrepreneurship and active citizenship through experimental learning: An interuniversity experience between two countries - Ortí Martínez, José Antonio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
As part of the European project Playeurope, the experiences of the students of the degrees in Early Childhood and Primary Education are wanted to know to raise awareness about the importance of being active citizens. The research carried out in 2022 retains a quantitative descriptive design, combined with qualitative aspects. There is a sample of two hundred students from Spain and Italy. The results deepen the lack of training in this regard at the university level. Having made the Success Stories Guide and the Guide to be a social entrepreneur has turned out to be a significant advance in the learning of future teachers.